SOCIAL INJUSTICE PRINCIPLES IN JENNY BICKS’S MOVIE SCRIPT THE GREATEST SHOWMAN ON EARTH 2015 - Nabila Fitria Fazrin; Ruminda Ruminda (Saksama, 2022)
This research aims to analyze the representation of social injustice in the film script of The Greatest Showman on Earth. The film, released in 2017, is a musical drama that tells the story of P.T. Barnum, a visionary who creates the Barnum & Bailey Circus and becomes one of the most famous showmen in the world. However, the film has received criticism for its depiction of social injustice, particularly in its representation of marginalized communities such as people of color and individuals with disabilities.The research will employ a qualitative analysis of the film script, focusing on the themes, characters, and storylines that address social injustice. The script will be analyzed for its accuracy in depicting the representation of social injustice principles.